Public safety in the conditions of martial law and mental warfare - S. O. Tkachenko; A. S. Diadin (Law and Safety)
The main purpose of the study is to develop proposals and concrete measures to strengthen public security in the conditions of martial law and mental war unleashed against Ukraine. The phenomenon of mental war during martial law and methods of influencing and countering informational attacks on the nation’s mentality have been studied. It has been established that mental warfare is an element of hybrid warfare and its informational component. Information war is a mental war, because it takes place, first of all, for people’s minds, and secondly, for their behavior.